Resourcefulness of cone beam computed sialography in detection of multiple radiolucent sialoliths: A case report - Tatu Joy Elenjickal; Indu Krishna; Raghupathy Lakshmana Perumal; Saumya Verma (Wolters Kluwer Medknow Publications, 2014)
Obstructive conditions of the salivary glands are common and may necessitate imaging of the gland for the purpose of diagnosis and management. Sialography is considered the gold standard for examining obstructive conditions of the parotid and submandibular glands but is largely influenced by the imaging technique to which it is coupled. The aim of this paper is to discuss the importance of cone beam computed sialography imaging which is a relatively new and very promising imaging modality in the detection of radiolucent sialoliths and to report a case of detection of radiolucent parotid sialoliths using cone beam computed sialography.